A sensitive method for the quantitation of the peptide-based glucagon-like peptide-1 receptor agonist liraglutide in plasma using microfluidics chromatography tandem MS. (5th March 2018) - King-Ahmad, Amanda J; Kalgutkar, Amit S; Niosi, Mark; Eng, Heather; Holliman, Christopher
Aim: An LC–MS/MS assay for the quantitation of liraglutide, a peptide-based injectable glucagon-like peptide-1 receptor agonist, has been developed as a convenient alternative to the enzyme-linked immunosorbent assay, and used to characterize liraglutide pharmacokinetics in cynomolgus monkeys.Results: Assay calibration curves exhibited a linear dynamic range of 10–5000 ng/ml and correlation coefficient ≥0.98. Following a 30 μg/kg intravenous dose, liraglutide demonstrated low plasma clearance and distribution volume, which led to a terminal half-life of 6.59 h in monkeys.Conclusion: The dynamic range of our LC–MS/MS assay provides sufficient coverage of the average efficacious liraglutide concentrations in human plasma, and can be used for pharmacokinetics/pharmacodynamics studies in animals and potentially in humans.